Residual-stress-induced crack formation in robocasted multi-material ceramics: Stress considerations and crack prevention - Wahl, Larissa; Cicconi, Maria Rita; Weichelt, Michelle; de Ligny, Dominique; Travitzky, Nahum (Journal of the European Ceramic Society, 2022)
Layered multi-material ceramics are natural candidates for modern engineering applications due to their attractive mechanical properties. Residual stresses caused, for example, by a thermal mismatch during the processing of these materials can significantly affect their mechanical properties. In this work, Raman investigations were performed to estimate these residual stresses in layered reaction-bonded silicon carbide (RBSC) and reaction-bonded boron carbide (RBBC) composites fabricated by robocasting. The Raman measurements show that the residual stress in the silicon phase of RBSC and RBBC composites has a different sign, which can explain the crack formation that occurred after Si infiltration. To adjust the stresses and prevent this cracking, a new paste composition was investigated. SEM micrographs and Raman measurements showed that almost crack-free layered composites with similar stresses in the different layers could be realized. In addition, well-known analytical approaches were used to calculate these residual stresses.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Raman spectroscopy; Reaction-bonded carbides; Residual stress; Robocasting